Peran Penyuluh dalam Kegiatan Budidaya Padi Sawah Organik dan Konvensional di Kecamatan Baula Kabupaten Kolaka - Marwanto, Intan; Rela, Iskandar Zainuddin; Nikoyan, Anas (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to determine the role of extension workers/assistant in cultivation activities in organic and conventional rice farming in Baula District, Kolaka Regency with a total of 17 informants. The method in this study uses qualitative analysis as suggested by Lexi J Moleong 2007, namely data reduction, data presentation, and initial conclusion drawing. The research results show that the role of extension workers/assistant in providing direct assistance in the field to organic farmers and conventional farmers and is assigned directly to assist farmers in carrying out cultivation activities, the difference lies in the method used.